A tecnologia no percurso de professores a atenção a si em processo de produção do conhecimento-subjetividade - Chagas, Maria de Fátima de Lima das (2013)
This dissertation is the result of an analysis of how a group of teachers conceive digital technologies and how these modes of perception become the route of training workshops in an educational environment. We start from the initial research question seeking to understand how modes of conceiving and producing with digital technologies transform the course of training workshops for teachers in a public school, emphasizing attention to you in the know - live process. As a working hypothesis, we believe that the meeting of teachers with digital technologies in an exercise experience of authorship, enhances the understanding of technology as a device that modifies the ways of life school, learning, knowledge. The experience of the workshops encouraged the development of research that we believe do with the subject teachers when they lend us their actions, experiences, emotions. The network of theoretical underpinning of the research studies considered the Biology of Cognition by Humberto Maturana and Francisco Varela (2011), the inventive knowledge perspective that brings in Henry Bergson (1979), understanding the relationship of Gilbert Simondon human - machine (1958, 1989) , known as the philosopher of technology and also the buildings on the modus operandi of care developed by Virginia Kastrup (2004, 2005) and Claudia Rodrigues de Freitas (2011). While intervention research, the methodological procedures involved the proposition workshops in which teachers interacted with digital technologies, conducted various productions related to its unique demands and their pedagogical activities and at the same time, the analysis of productions that are woven in the form of networks conversations in which teachers share the learning experience. Observed recurrences and movements of transformation referred to understand how the technologies in the construction of knowledge. We follow the inventive production pathways that allowed the observation and analysis of changes in networks built by teachers, cognitive processes referred to the way we perceive the technologies that we can observe in the coordination of gestures, ideas and emotions in the making. The enactive perspective of knowing that brings us Varela (2001) contended do the research we observe that emerged from be - do - knowing teachers. As a result of the work we distinguish cognitive processing referred to attentional processes in themselves do with digital technologies. By analyzing images, and written productions that make up this intervention study, we observed movements in which teachers, in the early stages of the workshops, gave visibility to a thrill of insecurity, fear of not knowing operate, anguish, a certain discomfort and resistance in producing with digital tools. Furthermore, the group of tools for use or disposal when no longer needed rejected the technology concept. In the course of the experience of the workshops, we have in ducts greater articulation in the interaction with digital technologies and changes in the way people feel and perceive when confidence in making himself steps in and interferes in our understanding of technology, now as a partner in circumstances of daily life